WISATA, FASILITAS, BIAYA PERJALANAN DAN PROMOSI PENGARUHNYA TERHADAP KUNJUNGAN WISATAWAN PADA OBYEK WISATA PANTAI PLENGKUNG DI KABUPATEN BANYUWANGI PROPINSI JAWA TIMUR (UPAYA PEMBERDAYAAN PENGUSAHA LOKAL SEKTOR PARIWISATA) - Ida Bagus Gede Udiyana; Putu Kepramareni; E. Erlinawati (Faculty of Economics and Business, Universitas Warmadewa, 2018)
Abstract The development of the tourism industry is currently growing very rapidly , giving competition atmosphere in the tourism industry. Various attempts were made by the government and other actors in the field of tourism services to make their area as an option for tourists . Therefore , please note that every traveler has a view or a different perception . In this study , the authors attempted to analyze the factors that affect tourist arrivals in tourist attraction â€œPlengkung Beachâ€ in Banyuwangi based on marketing mix ( product , place, , price and promotion ). The population in this study are tourists who were in Plengkung Beach . Techniques used in the sampling in this study with accidental sampling is a non-probability sampling . The number of samples taken 114 respondents . The method of data collection is done by dividing the questionnaire to the respondent to be filled. The analytical tool used in this study is OLS linear regression analysis using SPSS 16.0 , obtained from the data processing that a significant difference between the marketing mix with the number of tourists visiting the Plengkung Beach in Banyuwangi , while the variables that significantly proven affectly are service quality, facilities, travelling cost and promotion. Key words : service quality, tourist attraction, tourism facility, travelling cost, tourism promotion, tourist arrivals.